The Effect of Giving Butterfly Pea Flower Extract (Clitoria ternatea) on Reducing Cholesterol Levels and Histopathological Features of White Rat Testes (Rattus norvegicus) Wistar Male Obesity Model - Risnaldo Jaya; Andre Budi; Bungaran Sihombing (CV. Inara, 2024)
Obesity is a global, non-communicable condition that causes male infertility. Obesity impacts spermatogenesis and male fertility. Butterfly pea blossoms (Clitoria ternatea) contain antioxidants that fight free radicals and prevent obesity. This research looked at how butterfly pea flower extract (Clitoria ternatea) affected cholesterol levels, testicular function, and the histopathology of the testicles of obese male Wistar rats (Rattus norvegicus). This research is quantitative and uses a lab or actual experiment. The 24 test mice were randomly divided into four groups. The research data was analyzed using SPSS 25.0 for Windows. The normality test significance is 0.577. One-way ANOVA test results demonstrate 0.000 or greater than 0.05 significance. LSD post-hoc test values. The control and treatment groups 1–3 differed significantly (p = 0.000). No change was seen between treatment groups 2 and 3 (p = 0.088). The research found butterfly pea flower extract therapy (Clitoria ternatea) at 400mg and 600 mg/kgBW lowers cholesterol. Flavonoids, saponins, tannins, and triterpenoids reduce cholesterol and improve testicular function in obese white rats.